Characterization and analysis of new catalysts for a direct ethanol fuel cell - Mann, Jonathan (Langmuir : the ACS journal of surfaces and colloids, 2006)
A direct ethanol fuel cell offers an attractive, fairly high density, energy source, if an electrochemical system can be developed that efficiently carries out the 12-electron oxidation of ethanol to carbon dioxide and water. To that end, new catalyst systems must be developed along with fuel cell operating conditions that encourage the complete oxidation of ethanol, as opposed to the presently available platinum on carbon systems that tend to produce acetaldehyde (two-electron oxidation) or acetic acid (four-electron oxidation) products. It is found that a composite nanoparticulate catalyst containing platinum and tin oxide or platinum indium tin oxide allows the partial conversion of ethanol to its 12-electron oxidation products. Catalysts of this type can be formed using a modified polyol process. Elevation of the operating temperature of a proton exchange membrane fuel cell using the indicated catalysts to 130 degrees C facilitates the production of carbon dioxide and provides an improved current-voltage response